Teacher interpersonal behaviour in gifted students' Primary Science classrooms and effects on achievement - Lee, Yoke Cheng (Curtin University, 2010)
There is a strong tradition in classroom environment research involving investigations of associations between students’ outcomes (achievement and attitude) and the classroom learning environment. This study focuses on how the perception of Primary 5 (11-year-old) Gifted Education Programme (GEP) pupils on their science teacher could affect their cognitive achievement and attitude towards science. A sample of 279 students from 15 GEP classes from six (out of a possible nine) Singapore GEP primary schools participated in this study. The Questionnaire on Teacher Interaction (QTI) was employed to collect quantitative data.Qualitative data were also collected to complement the quantitative data. Research objectives in this study include determining the validity and reliability of the 48-item version QTI in primary science gifted classes and identifying the types of science teachers in the GEP in Singapore based on the Australian QTI-based typologies. The QTI covers eight scales of teacher behaviour. Generally, statistics showed that there is strong association between the Leadership scale and students’ attitude towards science. A teacher perceived highly by student on the Leadership scale would be confident and assertive in class. A strong association between the Strict scale and students’ cognitive achievement is also reported. In this study, no gender differences in the students’ perception of their teachers has been found.